As vilas: uma contribuição à história da arquitetura popular no Rio de Janeiro através do estudo do espaço urbano - Albernaz, Maria Paula (1985)
The labours villages and "avenidas", housing types that gave rise to the present "vilas", come from an ideological model appointed to control the working class standard of hygiene and morals, through their housing organization. At the end of the 19th century, the realization of this model became possible in Rio de Janeiro, taking into consideration the presence of certain conditions, such as: the great population increase; the existing areas subject to urban expansion; the possibilities of obtaining a revenue, constructing and renting houses; the implementation of factories; the appearing of a middle class among the population. In the suburb of Vila Isabel and its neighbournood, we have a very good example for the above conditions. Even nowadays we can fínd in Vila Isabel the "vilas", in an expressive number, due to the place and this housing type especifícities, and also because of its inhabitants' performance.